Sacred tropes : Tanakh, New Testament, and Qur'an as literature and culture - Sabbath, Roberta Sterman. (Biblical Interpretation Series, 2009)
Contemporary sacred text scholarship has been stimulated by a number of intersecting trends: a surging interest in religion, sacred texts, and inspirational issues; burgeoning developments in and applications of literary theories; intensifying academic focus on diverse cultures whether for education or scholarship. Although much has been written individually about Tanakh, New Testament, and Qur'an, no collection combines an examination of all three. Sacred Tropes interweaves Tanakh, New Testament, and Qur'an essays. Contributors collectively and also often individually use mixed literary approaches instead of the older single theory strategy. Appropriate for classroom or research, the essays utilize a variety of literary theoretical lenses including environmental, cultural studies, gender, psychoanalytic, ideological, economic, historicism, law, and rhetorical criticisms through which to examine these sacred works.